Challenging NICE guidelines on parathyroid surgery. Issue 4 (August 2022) - Zammit, Matthew; Pierce, Katriona; Bailey, Lisa; Rowland, Matthew; Waghorn, Alison; Shore, Susannah
Abstract: Background: National Institute of Clinical Excellence (NICE) recommend against routinely using Intra-Operative Parathyroid Hormone (IOPTH) for first-time parathyroid surgery due to its cost and minimal surgical benefit. The European Society of Endocrine Surgeons differ from this and recommends IOPTH with conflicting pre-operative or single imaging. NICE guidance acknowledged that this may change practice in larger centres. We devised a retrospective single-centre cohort study to analyse the impact of IOPTH on decision-making and cost-effectiveness. Methodology: First-time parathyroidectomy procedures for primary hyperparathyroidism were assessed between 2017 and 2019. Ultrasound (US) and Sestamibi with parathyroid single-photon emission with computed tomography (SPECT-CT) were compared with IOPTH. The contribution of IOPTH to cure and cost effectiveness ratio was calculated. Results: 114 cases were included, with IOPTH performed in all cases, SPECT-CT in 112 and US in 108 cases. A cure rate of 99.1% (113/114) was achieved. 11.4% (13/114) of the cure rate was influenced by IOPTH (P 0.01), instigating further exploration when its levels didn't decrease. This included 7.1% (4/56) in the concordant-imaging cohort. IOPTH accuracy (96.5%) was significantly superior (P = 0.03) to both US (80%) and SPECT-CT (81%). Comparing the total costs for IOPTH testing over 2 years (£39, 721) with 13 potential re-operative procedures in its absence (£63, 536), a positive cost-effectiveness ratio of £1832 per re-operative procedure averted was achieved. Conclusion: Abandoning IOPTH in first-time parathyroid surgery is too ambitious when weighing the cost of re-operative surgery against cost savings obtained by using routine IOPTH to achieve an improved cure rate, even in concordant imaging. Highlights: IOPTH was curatively responsible for 11.4% (13/114) of cases IOPTH accuracy was significantly superior to other imaging modalities studied A positive cost-effectiveness ratio supports feasibility for regular IOPTH use We propose routine IOPTH use in first-time parathyroid surgery. IOPTH = Intra-Operative Parathyroid Hormone.